Dependability evaluation of WirelessHART best practices - Ivanovitch Silva (2012)
WirelessHART currently appears as a promising solution for the last mile connection in process control applications. Most of these applications have stringent dependability requirements, where a system failure may result in economic losses, or damage for human life or the environment. Among the different type of faults that can lead to a system failure, permanent faults on network devices have a major impact. They can hamper communication over long periods of time and consequently they may disturb, or even disable, control algorithms with all resulting problems. In this work we perform a dependability evaluation of the best practices indicated by the HART Communication Foundation (HCF), when network devices are subject to permanent faults.